INVENTORY OF SHADE TREES IN GREEN OPEN SPACES IN TAMAN AHMAD YANI, TAMAN BERINGIN, TAMAN CADIKA IN MEDAN CITY - Ihsan Nur Harahap; Abdiyanto; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2024)
City parks are green open spaces (RTH) that have social, aesthetic, recreational, educational and other activity functions in urban areas, making them valuable assets for cities. Green open space is important for preserving the environment, mitigating climate impacts due to CO2 emissions, reducing air pollution, and increasing water absorption. The city of Medan, with an area of ​​281.99 km² and a population of 2,494,512 people, is facing serious problems due to imbalanced development which reduces green open space, increases emissions and air pollution, and the risk of flooding. According to Medan City Regional Regulation no. 1 In 2022, Medan has a green open space of 16.39% of the target of 20%, but the current condition has only reached 6.37%. Green open space is effective in reducing emissions, air pollution and flood risk, as well as providing recreational space. Green open space inventory with satellite imagery is important for real-time monitoring and better spatial planning. This research is needed to determine the condition and types of trees in various green open spaces in Medan City, including the number of trees, types of trees, types of shade trees, and tree stratification. This data will guide future greening strategies to benefit the environment and community well-being. Based on the inventory at Beringin Park, Ahmad Yani Park and Cadika Park, Medan City, there are a total of 1193 trees. In Ahmad Yani Park there are 222 trees with Raja Palm dominating 77 trees (34.68%) and Mahogany 35 trees (15.77%) and has 25 tree species with 20 types of shade trees, 47 large trees, 53 medium trees, and 122 small trees. Beringin Park has 183 trees with Mahogany dominating with 67 trees (36.61%) and Trembesi with 25 trees (13.66%) and has 25 tree species with 21 types of shade trees, 11 large trees, 20 medium trees, and 23 trees. small. Cadika Park has 788 trees with Ketapang Kencana dominating with 135 trees (17.13%) and Mahogany with 109 trees (13.83%) and has 40 tree species with 35 types of shade trees, 164 large trees, 250 medium trees, and 374 small tree. Identification of tree canopy width shows that 216 trees in Medan City have a canopy width of 4 meters, 68 trees have the smallest canopy width of 2 meters, and the trees with the largest canopy width are Angsana and Pulai in Ahmad Yani Park with a canopy width of 25 meters.